Growth and yield of rice as influenced by different levels of temperature, water and nitrogen under greenhouse condition - Pauline Niyomugabo; Dilys Sefakor MacCarthy; Samuel Godfried Kwasi Adiku (Cogent Food & Agriculture)
Increasing temperature and frequency of drought associated with climate variability and change and low soil fertility are factors that handicap sustained rice (Oryza sativa L) production in the tropics. In this study, the growth and yield of rice (Legon 1 rice variety) were investigated under three temperature regimes T1 = 33 °C, T2 = 34 °C, and T3 = 36 °C, two water regimes W1 = continuous flooding and W2 = intermittent irrigation, and two nitrogen application rates: (N1 = 0 kg N ha−1 and N2 = 90 kg N ha−1) at the Soil and Irrigation Research Centre, of the University of Ghana, Ghana. The experimental design was split-plot with temperature treatments as main plots and water and nitrogen applications as subplots with 4 replicates. The rice plants under high temperatures (T3 & T2) produced significantly lower biomass, nutrient uptake, and grain yield. Furthermore, the intermittent irrigation (W2) and nitrogen application (N2) significantly increased the percentage of yield components, grain yield, and nutrient uptake, The intermittent irrigation saved between 20 and 33% of irrigation water. The grain yield under the intermittent irrigation was 36, 24, and 15 g pot−1 for T1, T2, and T3, respectively, compared with 22, 14, and 8 g pot−1 for T1, T2, and T3 under the full continuous irrigation conditions. The uptake of nutrients was lower under the increased temperature with the rate of decline higher under nitrogen fertilization. The potential decline in grain quality due to reduced nutrient uptake poses a challenge for human nutrition under warmer climates.